The Sustainability and Challenges of Business Incubators in the Western Cape Province, South Africa - Thobekani Lose (Sustainability, 2015)
Notwithstanding the growing interest in business incubation programmes and the benefits derived from such programmes, the path is beset by numerous challenges. This paper investigates the challenges faced by business incubators (BIs) as they strive to support their clients. The study utilized a qualitative approach to collect data by way of interviews to gain in-depth knowledge and understanding of the concept and challenges of business incubators. The data were collected using structured and unstructured in-depth personal interviews, which were carried out with the respondents of business incubators in the Western Cape. The research participants for this study were limited to the business incubators on the database of a local organization that promotes small and medium enterprises (SMEs) development strategy and programmes in the Western Cape Province. All five business incubators on the database were deemed suitable for the study. The results indicated that an average of twenty-five entrepreneurs graduated from the incubation programme in the last five years. Furthermore, lack of sponsorship, production space, advanced technological facilities (prototype) and expansion to different areas were found to be among the challenges hindering incubators.